Triplet state of 4-methoxybenzyl alcohol chemisorbed on silica nanoparticles - Arce, Valeria Beatriz (2012)
The knowledge of photochemical kinetics in colloidal systems is important in understanding environmental photochemistry on dispersed solid surfaces. As model materials for the chemically sorbed organic compounds present in natural environments, modified silica nanoparticles (NPs) were obtained here by condensation of the silanol groups of fumed silica nanoparticles with 4-methoxybenzyl alcohol. These particles were characterized by different techniques. To evaluate their toxicity, the inhibition of the natural luminescence emission of the marine bacterium Vibrio fischeri in suspensions of the particles was measured. Laser flash-photolysis experiments (λexc = 266 nm) performed with NP suspensions in acetonitrile-aqueous phosphate buffer mixtures showed the formation of the lowest triplet excited state of the chemisorbed organic groups (λmax = 390 nm). DFT calculations of the absorption spectrum of this radical support the assignment. From the calculated triplet energy, a thermodynamically favorable energy transfer from these triplet states to oxygen to yield singlet molecular oxygen is predicted. Avalue of 0.09 was measured for the quantum yield of singlet molecular oxygen generation by air-saturated suspensions of the nanoparticles in the mixture of solvents acetonitrile-aqueous phosphate buffer. The quantum yield of singlet molecular oxygen generation by the free 4-methoxybenzyl alcohol in the same solvent is 0.31.